2021
DOI: 10.3389/fvets.2020.625067
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomic Profiles of Paratuberculosis Infected and Infectious Dairy Cattle by Ambient Mass Spectrometry

Abstract: Mycobacterium avium subsp. paratuberculosis (MAP) is the causative agent of paratuberculosis [Johne's disease (JD)], a chronic disease that causes substantial economic losses in the dairy cattle industry. The long incubation period means clinical signs are visible in animals only after years, and some cases remain undetected because of the subclinical manifestation of the disease. Considering the complexity of JD pathogenesis, animals can be classified as infected, infectious, or affected. The major limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…Few studies have used omic techniques to study MAP, particularly metabolomics, despite their ability to demonstrate the dynamics of infection and highlight potential diagnostic biomarkers. Previous studies examining the metabolomics of MAP using NMR and DART-HRMS highlighted significant energy deficits alongside altered fat metabolism in experimentally and MAP-infected cattle [19,20]. In this study, we observed five metabolites which discriminated between naturally MAP-infected and control heifers consistently from 1 to 19 months of age (Figure 4); clearly, these metabolites will require validation with further experimentation.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Few studies have used omic techniques to study MAP, particularly metabolomics, despite their ability to demonstrate the dynamics of infection and highlight potential diagnostic biomarkers. Previous studies examining the metabolomics of MAP using NMR and DART-HRMS highlighted significant energy deficits alongside altered fat metabolism in experimentally and MAP-infected cattle [19,20]. In this study, we observed five metabolites which discriminated between naturally MAP-infected and control heifers consistently from 1 to 19 months of age (Figure 4); clearly, these metabolites will require validation with further experimentation.…”
Section: Discussionmentioning
confidence: 52%
“…This was partially in contrast to previous studies. Tata et al [20] reported an increase in creatine/creatinine in MAP-infected and infectious cattle but a decrease in urea within infectious cattle. However, de Buck et al [19] demonstrated a significant increase in urea but a decrease in creatinine within MAP-inoculated cattle.…”
Section: Key Metabolites Suggest Uraemic Changes That May Be Indicative Of Th1-th2 Switchesmentioning
confidence: 98%
See 1 more Smart Citation
“…In the field of clinical chemistry, we have defined the characteristic profiles of sera from cows affected by paratuberculosis to accelerate the early diagnosis of this bovine pulmonary disease. 8 In regards to routine microbial diagnostics, we have set up rapid screening approaches for Legionella pneumophila serotyping that aim to guide the selection of conventional methods, with subsequent reduction of the microbiology laboratory costs and times. 9 Our activities as a test laboratory According to EU regulation, manufacturers of processed foods are required to provide a nutrition fact label for each product that reports the energy value (kcal/kJ), and amounts of fat, saturated fatty acid, carbohydrate, sugar, protein, and salt.…”
Section: Our Achievementsmentioning
confidence: 99%
“…In the field of clinical chemistry, we have defined the characteristic profiles of sera from cows affected by paratuberculosis to accelerate the early diagnosis of this bovine pulmonary disease. 8 In regards to routine microbial diagnostics, we have set up rapid screening approaches for Legionella pneumophila serotyping that aim to guide the selection of conventional methods, with subsequent reduction of the microbiology laboratory costs and times. 9…”
Section: Our Achievementsmentioning
confidence: 99%